2014
DOI: 10.1017/s1755048314000455
|View full text |Cite
|
Sign up to set email alerts
|

Does Interviewer Religious Dress Affect Survey Responses? Evidence from Morocco

Abstract: Few studies examine religiosity-of-interviewer effects, despite recent expansion of surveying in the Muslim world. Using data from a nationallyrepresentative survey of 800 Moroccans conducted in 2007, this study investigates whether and why interviewer religiosity and gender affect responses to religiously-sensitive questions. Interviewer dress affects responses to four of six items, but effects are larger and more consistent for religious respondents, in support of power relations theory. Religious Moroccans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…Previous research has shown that survey responses are associated with enumerator characteristics such as gender (Huddy et al, 1997;Flores Macias and Lawson, 2008), religion (Blaydes and Gillum, 2013;Benstead, 2014), ethnicity (Adida et al, 2016), experience and personality traits (Jäckle et al, 2013), differences in social status with the respondent (Kane and Macaulay, 1993), or even physical attractiveness (Jaeger, 2016).…”
Section: Literaturementioning
confidence: 99%
“…Previous research has shown that survey responses are associated with enumerator characteristics such as gender (Huddy et al, 1997;Flores Macias and Lawson, 2008), religion (Blaydes and Gillum, 2013;Benstead, 2014), ethnicity (Adida et al, 2016), experience and personality traits (Jäckle et al, 2013), differences in social status with the respondent (Kane and Macaulay, 1993), or even physical attractiveness (Jaeger, 2016).…”
Section: Literaturementioning
confidence: 99%
“…Moreover, these characteristics can have interaction effects. More recent research (Benstead, 2013(Benstead, , 2014 demonstrated an interaction of interviewer effects between gender and religiosity (operationalized as wearing hijab) in Morocco, as religious respondents reported differently to an unveiled interviewer.…”
Section: Perhaps the Most Researched Interviewer Effect In The Literamentioning
confidence: 99%
“…In MENA, clothing expresses individual, family, and community identity, and conservatism or religion (Benstead 2014). Women's styles range from jeans and tunics modified with a headscarf (hijab) to a scarf and loose coat worn over clothing (djlabah), occasionally with a face veil (niqab).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%